DAMPAK PENGGUNAAN MEDIA SOSIAL TIKTOK TERHADAP MORALITAS REMAJA - Kusuma, Uum (UNTIRTA CIVIC EDUCATION JOURNAL, 2023)
This research was conducted in the Ciwaru Masjid neighborhood, Cipocok Jaya District, with the aim of 1) To find out the Efforts to Overcome the Impact of Tik Tok Social Media Use on Youth Morality in the Ciwaru Masjid neighborhood, Cipocok Jaya Village. 2) Knowing the Impact of Tik Tok Social Media on Youth Morality in the Ciwaru Mosque, Cipocok Jaya Village. The method used is a qualitative method with data collection through observation, interviews and documentation techniques. The analysis used is by using triangulation with data reduction techniques, data display and data verification. The results obtained in this study are that the community and parents have made efforts to apply disciplined attitudes quite well by providing positive guidance attitudes to adolescents in playing social media, applying appropriate rules and sanctions for children, implementing coaching education in the use of social media. Tik Tok. While the impact that affects the inhibition of morality on adolescents in the use of Tik Tok. Children become individual or apathetic, narcissistic behavior that favors itself, reduced the value of mutual cooperation and is not sensitive to the community environment. Which is influenced by two factors, namely internal and external where the internal comes from within the child himself such as will, and habits. While external factors come from the learning environment, as well as the social environment.